THE BUSINESS JUDGMENT RULE AS LEGAL PROTECTION FOR DIRECTORS IN BUSINESS DECISION-MAKING - Meylinda; Siti Nurhayati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Business Judgment Rule (BJR) doctrine is an essential pillar of corporate governance. However, its implementation in Indonesia creates legal uncertainty, particularly for Directors of State-Owned Enterprises (SOEs) who are vulnerable to the criminalization of business decisions as corruption offenses. This study aims to comparatively analyze the implementation of the BJR in Indonesia through an international perspective (Delaware) to identify key challenges. Employing a normative-juridical method with comparative, statutory, and case study approaches, this research maps fundamental differences. The analysis reveals three distinct gaps: (1) A procedural gap, where Indonesia's BJR (Article 97(5) of the Company Law) functions as an affirmative defense rather than a presumption of protection as seen in common law jurisdictions; (2) A functional gap, namely the shift of the BJR’s function from the civil realm to a criminal defense (mens rea); and (3) A contextual gap, where SOE business losses are interpreted as “state losses.” The contrasting dynamics of court decisions (the case of the former President Director of PT. Pertamina vs. Jiwasraya) highlight the failure of the BJR to distinguish error of judgment from bad faith. Consequently, directors tend to become risk averse. This study recommends legislative clarification, harmonization among law enforcement agencies, and the strengthening of internal governance to restore legal certainty.